One year clinical outcomes in patients with insulin-treated diabetes mellitus and non-insulin-treated diabetes mellitus compared to non-diabetics after deployment of the bio-engineered COMBO stent. (1st January 2017) - Kalkman, Deborah N.; Woudstra, Pier; den Heijer, Peter; Menown, Ian B.A.; Erglis, Andrejs; Suryapranata, Harry; Arkenbout, Karin E.; Iñiguez, Andrés; van 't Hof, Arnoud W.J.; Muller, Philippe; Tijssen, Jan G.; de Winter, Robbert J.
Abstract: Background: The COMBO stent is a novel sirolimus-eluting stent with a luminal anti-CD34 + antibody layer to promote vessel healing. No data is currently available on clinical outcomes after treatment with this novel bio-engineered device in diabetic patients. We evaluate clinical outcomes at twelve months after COMBO stent placement in patients without diabetes mellitus (non-DM), patients with non-insulin-treated diabetes mellitus (nITDM) and patients with insulin-treated diabetes mellitus (ITDM). Methods: This study is a pre-specified subgroup analysis of the 1000 patient all-comers REMEDEE Registry. The primary endpoint is target lesion failure (TLF), which is a combined endpoint consisting of cardiac death, target vessel-myocardial infarction (tv-MI) and target lesion revascularization (TLR) at twelve months follow-up. Kaplan Meier method is used with log rank to compare outcomes between groups. Results: This subgroup analysis includes 807 non-DM, 117 nITDM and 67 ITDM. Kaplan–Meier estimates for TLF at twelve months are 4.4% in non-DM, 6.8% in nITDM and 20.3% in ITDM, p < 0.001 (non-DM vs nITDM p = 0.244, non-DM vs ITDM p < 0.001). Conclusions: This study gives the first insight into the impact of insulin-treated diabetes mellitus on clinical outcome of patients treated with the novel COMBO stent. At one year after COMBO stent placement significantly higher rates of target lesion failure are seen in patients with ITDM compared to patients with nITDM and patients without DM.